SOCIO-CULTURAL AND LEGAL CHANGES IN INDONESIA - Syarhan, Mohamad (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2021)
In terms of its form, the law can be in the form of written law and can also be unwritten law. The purpose of this study is to analyze the influence of socio-cultural aspects on legal changes in Indonesia. The research method used is normative legal research. The results of the study show that talking about legal culture is the same as talking about public legal awareness. These two things are an inseparable unit, because they are closely related to the implementation of law in society. Thus, legal culture and legal awareness are two things that can be developed properly in an integrated manner so that the legal reforms implemented can be accepted by the community as behavioral guidelines that must be followed.